2002
DOI: 10.1002/cncr.10208
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of color doppler ultrasound in patients with endometrial hyperplasia and carcinoma

Abstract: At the microstructural level, bones remodel throughout life. This process is recorded in bone cortex as osteons. A more comprehensive understanding of the interaction between genetic regulation and environmental factors in osteon remodeling will increase the value of this skeletal record and enable more accurate reconstruction of individual life histories. The purpose of this study was to examine the contribution of maternal lineage to normal age and sex variation in osteon remodeling dynamics in Macaca mulatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 211 publications
1
16
0
2
Order By: Relevance
“…Some studies have assessed the blood flow characteristics of the uterine artery, 17,11 whereas others have evaluated directly the blood flow characteristics of intratumoral arteries. 26,27 Cheng et al 26 have shown the usefulness of TV-CDU in predicting myometrial tumor spread by using blood flow resistance indices. 28 However, Develioglu et al 17 have shown the unreliability of predicting tumor spread using such indices.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have assessed the blood flow characteristics of the uterine artery, 17,11 whereas others have evaluated directly the blood flow characteristics of intratumoral arteries. 26,27 Cheng et al 26 have shown the usefulness of TV-CDU in predicting myometrial tumor spread by using blood flow resistance indices. 28 However, Develioglu et al 17 have shown the unreliability of predicting tumor spread using such indices.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, the usefulness of this parameter to discriminate between benign and malignant endometria has shown contradictory results. 3,4 A progressive increase in angiogenesis has been implicated in the progression from endometrial hyperplasia to invasive carcinoma, 5 and color Doppler sonography is a technique that allows in vivo assessment of tumoral angiogenesis. 6 Both premises can explain why this examination has been proposed for discriminating between benign and malignant endometria [7][8][9][10][11][12] and to predict tumoral extension before surgery.…”
mentioning
confidence: 99%
“…Le rôle du Doppler pulsé ou couleur dans l'évaluation de l'invasion myométriale est controversé [19,[25][26][27]. Le cancer de l'endomètre s'associe à une hypervascularisation voire une néovascularisation endométriale et sous-endométriale, avec une diminution des index de résistance (IR) et des index de pulsatilité de l'artère utérine, ainsi qu'une perte de l'encoche protodiastolique.…”
Section: Discussionunclassified